CT image evaluation of one-screw fixation in the Latarjet procedure. (December 2020) - Omae, Hiromichi
Abstract: Background: In the Latarjet procedure, two screws are used for secure fixation. However, when the graft is small, two-screw fixation is technically difficult. The purpose of this study was to evaluate the bone union of one-screw fixation on CT images. Methods: Ten shoulders with anterior recurrent dislocation underwent the open Latarjet procedure using one-screw fixation combined with arthroscopic Bankart repair. The bone union and the graft position were evaluated on CT images at 3, 6, and 12 months after the operation. Results: Seven of 10 shoulders showed bone union at 3 months after the operation. In two shoulders, the removal of cortex was insufficient, and bone union was observed at 6 months. In one shoulder, the distal part of the graft was not in contact with the glenoid, and bone union was observed at 12 months. In one shoulder, the graft was healed in a 70-degree-rotated position. The average thickness of the graft was 7.2 ± 1.0 mm. Conclusion: One-screw fixation in the Latarjet procedure did not show non-union. Sufficient removal of the graft cortex and good contact were needed for early union.